Damage and Failure of Aeroengine Blades Under Small UAV Impacts - Zhibin Wu; Chi Chen; Feiying Chen; Jun Liu (International Journal of Aerospace Engineering)
Unmanned aerial vehicles (UAVs) may collide with vulnerable parts of other aircrafts, such as engine blades, causing accidents. The research on small UAV impact is limited. Besides, UAV impact with propeller and rotor blades is poorly understood. In this paper, a finite element (FE) model of a UAV with a weight of 4.78 kg, turbofan blades, propeller blades, and helicopter tail rotor blades was developed. The FE modelling was carried out by commercial software named LS-DYNA R13.1.0, which is one of the most advanced simulation tools for nonlinear dynamic structural analysis, mainly solving numerical simulations of collision and penetration problems. First, the UAV FE model was validated by comparing the simulation results against the experiments. Next, simulations were conducted to investigate the damage of the three blades under UAV impact with different heading angles. The damage type and effect of UAV’s heading angle were analyzed and identified. The simulation results indicated that the turbofan blades experienced the more severe damage, compared with the propeller blades and tail rotor blades. The head orientation of the UAV has a significant effect on the impact force of the three aircraft engine blades. In addition, certain parts of the UAV (e.g., battery) can produce significant damage to the blades. The research findings are helpful for the safety assessment of the UAV impact damages to different aircraft engines.